Effectiveness of Kiambang Plant (Salvinia molesta) in Phytoremediation of Copper (Cu) Heavy Metal at Various Concentrations (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
This study aimed to determine the effectiveness of the kiambang plant (Salvinia molesta) in reducing copper (Cu) heavy metal concentrations in water bodies through phytoremediation. Copper concentrations of 3 ppm, 6 ppm, 9 ppm, 12 ppm, and 15 ppm were applied, and observations were conducted over seven days using a UV-Vis spectrophotometer at a wavelength of 445 nm. The results showed a significant effect of Cu concentration variation on the plant’s phytoremediation capacity, as indicated by the One Way ANOVA test (F-count 73.064 > F-table 3.05; p < 0.05). The highest remediation efficiency was observed at the 15 ppm concentration. Kiambang plants proved effective as phytoremediation agents in mitigating copper heavy metal pollution in aquatic environments.